The Effect of Diabetes Self-Management Education on Self-Empowerment of Patients with Type 2 Diabetes Mellitus in the Susut I Public Health Center - Pawitra, I Ketut Arya; Pramesti, Theresia Anita; Saraswati, Ni Luh Gede Intan (Future Science, 2025)
Introduction: The increasing cases of diabetes mellitus (DM) every year indicate suboptimal disease management by DM patients. One contributing factor is the lack of confidence among patients in conducting self-health care (self-empowerment). Education through DSME is believed to improve the self-empowerment of DM patients. Objective: This study aims to determine the effect of DSME on the self-empowerment of type 2 DM patients in the Susut I Community Health Center working area. Methods: This study employs a pre-experimental design with a one-group pre-posttest approach, where respondents received DSME intervention four times. The population consisted of 93 individuals, and a sample of 22 respondents was selected using purposive sampling. Data collection was conducted using the Diabetes Empowerment Scale (DES) questionnaire and analyzed using the Wilcoxon Signed-Rank Test with a significance level of 0.05%. Results: The pretest results showed that the majority of respondents had moderate self-empowerment, accounting for 16 individuals (72.73%), while six individuals (27.27%) had low self-empowerment. The posttest results indicated that the majority of respondents had moderate self-empowerment, accounting for 17 individuals (77.27%), while five individuals (22.73%) achieved good self-empowerment. Data analysis revealed a p-value of 0.001 (p < α; α = 0.05), indicating a significant effect of DSME implementation on type 2 diabetes mellitus patients in the Susut I Community Health Center working area. Conclusion: Providing appropriate education can enhance the confidence of diabetes patients in making informed decisions tailored to their needs, expand their knowledge to foster new mindsets, and increase their willingness and readiness to prevent complications, plan meals, engage in regular physical activity, and take medication consistently. This can guide diabetes patients toward a state of well-being with good empowerment.